HIMARS MENGAJAR CUCI TANGAN MENUJU KESEHATAN YANG HEBAT - Mahardhika, Rosliana; Rian Saputro, Dafid (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
he community service activity themed “Handwashing Towards Great Health” was conducted at SDN Grantung on April 19, 2025, as an effort to promote health and encourage clean living behavior among elementary school students. This activity was motivated by the importance of handwashing as a preventive measure against infectious diseases, while many students still lacked knowledge of proper handwashing techniques. The methods included preparation and coordination, interactive health education, demonstration of the six steps of proper handwashing according to WHO standards, interactive quizzes, and evaluation through pre-test and post-test. The results showed a significant improvement in students’ knowledge and skills. Before the intervention, only a few students understood the correct handwashing steps, while after the program, the majority were able to explain and practice them accurately. The conclusion highlights that interactive and practice-based education methods are effective in improving students’ understanding and can foster sustainable healthy habits. Future recommendations include continuous teacher supervision and the provision of adequate handwashing facilities to ensure the long-term adoption of this behavior.